2022
DOI: 10.1111/dmcn.15377
|View full text |Cite
|
Sign up to set email alerts
|

Antiseizure medication reduction and withdrawal in children with drug‐resistant epilepsy after starting the ketogenic diet

Abstract: Aim: To investigate the rate of successful withdrawal of antiseizure medication (ASM) after starting the ketogenic diet in children and identify predictive factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The underlying mechanism that explains the broad‐spectrum efficacy of KDT is rather multifaceted. Consistent with a previous study, 16 we also observed seizure worsening when reducing ASMs, but it was usually temporary and rarely led to the consequence of adding back the medications. This suggests that the temporary seizure worsening observed during medication reduction does not impact the long‐term outcome of KDT.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The underlying mechanism that explains the broad‐spectrum efficacy of KDT is rather multifaceted. Consistent with a previous study, 16 we also observed seizure worsening when reducing ASMs, but it was usually temporary and rarely led to the consequence of adding back the medications. This suggests that the temporary seizure worsening observed during medication reduction does not impact the long‐term outcome of KDT.…”
Section: Discussionsupporting
confidence: 91%
“…Successful withdrawal or reduction of an ASM was defined as a period exceeding 3 months, during which the medication was permanently discontinued or reduced in dosage without the necessity to restart, increase, or initiate any new ASMs throughout the entire follow‐up period (≥9 months). 16 The treatment outcome of KDT was classified as non‐response when the frequency of seizures decreased by less than 50% compared to baseline and as response if the reduction rate was equal to or greater than 50%. The seizure severity after KDT was evaluated according to the patient's seizure diary and was compared to it before treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cognitive improvement may occur in the setting of improved seizure frequency, it is also interesting to note that cognitive improvement has been seen following the use of ketogenic interventions in patients with mild cognitive impairment and Alzheimer's disease [35,37]. A study found that following 3-6 months of the ketogenic diet, 63% of patients tolerated a successful withdrawal of at least one antiseizure medication (ASM) [38,39]. Younger age at initiation of the ketogenic diet was a predictor of successful ASM withdrawal [38].…”
Section: Benefits Beyond Seizure Controlmentioning
confidence: 99%
“…A study found that following 3-6 months of the ketogenic diet, 63% of patients tolerated a successful withdrawal of at least one antiseizure medication (ASM) [38,39]. Younger age at initiation of the ketogenic diet was a predictor of successful ASM withdrawal [38].…”
Section: Benefits Beyond Seizure Controlmentioning
confidence: 99%